2016
DOI: 10.1111/xen.12274
|View full text |Cite
|
Sign up to set email alerts
|

Xenograft of microencapsulated Sertoli cells restores glucose homeostasis in db/db mice with spontaneous diabetes mellitus

Abstract: Preliminarily, xenograft of MC-SC holds promises for an effective cell therapy approach for treatment of experimental T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In association with these results, a significant upregulated expression of the adipose tissue uncoupling protein 1 (UCP‐1) was demonstrated along with a consistent increase in regulatory B cells and anti‐inflammatory macrophages, while pro‐inflammatory macrophages decreased. iNOS and pro‐inflammatory molecules diminished in the treated animals while levels of anti‐inflammatory cytokine IL‐10 and circulating adiponectin increased (Luca et al ., ,b). After transplantation, the anti‐hyperglycemic effects were associated with a downregulated expression of GLUT‐2 and an upregulated expression of GLUT‐4 in the liver and skeletal muscle, respectively (Luca et al ., ,b).…”
Section: Current Applications Of Sertoli Cells To Transplantation: Prmentioning
confidence: 99%
See 2 more Smart Citations
“…In association with these results, a significant upregulated expression of the adipose tissue uncoupling protein 1 (UCP‐1) was demonstrated along with a consistent increase in regulatory B cells and anti‐inflammatory macrophages, while pro‐inflammatory macrophages decreased. iNOS and pro‐inflammatory molecules diminished in the treated animals while levels of anti‐inflammatory cytokine IL‐10 and circulating adiponectin increased (Luca et al ., ,b). After transplantation, the anti‐hyperglycemic effects were associated with a downregulated expression of GLUT‐2 and an upregulated expression of GLUT‐4 in the liver and skeletal muscle, respectively (Luca et al ., ,b).…”
Section: Current Applications Of Sertoli Cells To Transplantation: Prmentioning
confidence: 99%
“…iNOS and pro‐inflammatory molecules diminished in the treated animals while levels of anti‐inflammatory cytokine IL‐10 and circulating adiponectin increased (Luca et al ., ,b). After transplantation, the anti‐hyperglycemic effects were associated with a downregulated expression of GLUT‐2 and an upregulated expression of GLUT‐4 in the liver and skeletal muscle, respectively (Luca et al ., ,b). Additionally, Luca and colleagues also demonstrated that the i.p.…”
Section: Current Applications Of Sertoli Cells To Transplantation: Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplantation of pancreatic β‐cells, thermogenic, fetal and genetically modified adipocytes, and other minor cell populations showed therapeutic promise for treatment of many degenerative disorders including diabetes and obesity. However, systemic and immune effects in vivo limit possibilities to dissect mechanisms for interaction between xenograft and host organism.…”
Section: Discussionmentioning
confidence: 99%
“…Xenotransplantation of organs, specific cell populations, and genetically engineered cells continue to be investigated to address shortage of donor organs and for the treatment of genetic, autoimmune, and degenerative diseases . The survival and longevity of xenografts depend on interaction with the host immune system as well as an ability to integrate into the host's metabolism and energy pathways.…”
Section: Introductionmentioning
confidence: 99%